Off-Reserve Employment Options For On-Reserve First Nations In Canada - Lashley, Phillip; Olfert, M. Rose (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2013)
Alternative land management options for First Nations are intended to improve their well-being through on-Reserve economic development. Another means by which First Nations are increasing their participation in the economy is through migration off Reserve, primarily urban centres. A third, to date neglected, means by which First Nations participate in the economy is through accessing off-Reserve employment while retaining Reserve residence. While positive urban agglomeration spillovers in the form of employment opportunities for rural populations are well established for the general population, this has not been investigated for Reserve populations. This paper examines the incidence and determinants of off-Reserve employment by Reserve residents in Canada. We find that along with distance, population growth rates and a higher percentage of the population over the age of 15, out-commuting rates from Reserves are influential in Community Well-Being Scores. Out-commuting is, in turn, facilitated by high school completion rates and negatively affected by distance. We conclude that improved access to off-Reserve employment for Reserve residents is an important means of improving the well-being of Reserve populations, and that a high school education is associated with off-Reserve employment.